2022
DOI: 10.1037/pst0000417
|View full text |Cite
|
Sign up to set email alerts
|

A pilot test of a treatment to address intersectional stigma, mental health, and HIV risk among gay and bisexual men of color.

Abstract: We tested the feasibility and acceptability of a group therapy treatment that addresses the intersecting stigma-related stressors theorized to drive elevated mental health risk, sexual health risk, and their co-occurrence among Black and Latino gay, bisexual, and other men who have sex with men (GBM). First, we modified an existing 10-week, one-on-one, cognitive–behavioral treatment addressing co-occurring health risks among GBM to develop a group-based, intersectionally informed treatment for GBM of color. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 96 publications
0
37
0
Order By: Relevance
“…In combination, this suggests that psychological outcomes may be worse for LGBTQI people with cancer than has previously been estimated ( 106 ) as there has been a dearth of research that included TGD, AYA and intersex people with cancer, as well as those who identified as bisexual or queer ( 1 ). These differences in health outcomes in LGBTQI sub-groups are reflected in differences in the psycho-social concomitants of distress and QOL, which can be conceptualized as intersecting stigma-related stressors ( 107 ). TGD, intersex, AYA, queer and bisexual subgroups reported higher levels of a number of these stressors, including discomfort with being LGBTQI, discrimination in life and in cancer care, lower outness, greater impact of cancer on LGBTQI identity and gender identity, and lower social support, likely contributing to their higher distress and poorer QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination, this suggests that psychological outcomes may be worse for LGBTQI people with cancer than has previously been estimated ( 106 ) as there has been a dearth of research that included TGD, AYA and intersex people with cancer, as well as those who identified as bisexual or queer ( 1 ). These differences in health outcomes in LGBTQI sub-groups are reflected in differences in the psycho-social concomitants of distress and QOL, which can be conceptualized as intersecting stigma-related stressors ( 107 ). TGD, intersex, AYA, queer and bisexual subgroups reported higher levels of a number of these stressors, including discomfort with being LGBTQI, discrimination in life and in cancer care, lower outness, greater impact of cancer on LGBTQI identity and gender identity, and lower social support, likely contributing to their higher distress and poorer QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Minority stress theory ( 61 ) explains the link between stigma-related distal stressors in a person’s environment, such as LGBTQI discrimination, social rejection, homophobia and transphobia, and health. Research drawing on this framework suggests that living in a hostile, discriminatory context can elicit internal, health-eroding proximal stress processes related to individuals’ minority status, including anxious expectations of rejection, identity concealment, and internalized stigma ( 107 , 146 ). This is reflected in the chronic stress experienced by LGBTQI people, as the result of stigmatization and discrimination within heterosexist and transphobic societies ( 147 , 148 ).…”
Section: Discussionmentioning
confidence: 99%
“…This wait-list-controlled trial establishes the preliminary efficacy of training mental health providers to deliver LGBTQ-affirmative CBT, an intervention with increasing empirical evidence for improving LGBTQ people's mental health (Jackson et al, 2022;Pachankis et al, 2020;Pachankis, Harkness, et al, 2022). In this study, mental health providers working at LGBTQ community centers across the U.S., Canada, and Uganda were trained to deliver this treatment that applies CBT tenets to addressing the cognitive, affective, and behavioral targets through which minority stress undermines LGBTQ people's mental health (Pachankis, Soulliard, et al, 2022).…”
Section: Discussionmentioning
confidence: 80%
“…LGBTQ-affirmative adaptations were generated through deep consultation with LGBTQ community members and clinical experts (Pachankis, 2014;Pachankis, Soulliard, et al, 2022;Scheer et al, in press). The treatment has been effectively delivered in individual and group formats and implemented in community-based clinics (e.g., Jackson et al, 2022;Pan et al, 2021), supporting its promise for broader implementation beyond the controlled trials in which it was originally developed and tested. Broader implementation of evidence-based practice can be achieved by training providers in such practice (Lehane et al, 2019) and training providers to deliver LGBTQ-affirmative evidence-based care, specifically, represents a promising way to reduce the barriers to LGBTQ-affirmative mental health care described above.…”
Section: What Is the Public Health Significance Of This Article?mentioning
confidence: 91%
See 1 more Smart Citation